k-error linear complexity of binary cyclotomic generators - Zhixiong CHEN; Chenhuang WU (Tongxin xuebao)
In terms of the discrete Fourier transforms,the k-error linear complexities over F2were discussed for Legendre,Ding-Helleseth-Lam,and Hall's sextic residue sequences of odd prime period p.More precisely,the 1-error linear complexities of these sequences were determined.Then,with some special restrictions of the order of 2 modulo p,partial results on their k-error linear complexities (k≥2) were proved.